RECONSTRUCTION OF INDONESIAN LABOUR REGULATION TO THE INTERESTS WORKERS IN INDONESIA (Reviewing About Salary) - Budiyono Budiyono (UNISSULA, 2018)
Workers protection is intended to guarantee the basic rights of workers and ensure equality of opportunity and treatment without discrimination on any basis whatsoever for the welfare of workers and their families with regard to the progress of the business world. In Part Two of Article 88 of Act No. 13 of 2003 which regulates the Wage has been set that the government set a wage policy that protects workers in Article 88 paragraph (2) with the hope of every worker is entitled to the income that meets a decent livelihood for humanity in Article 88 paragraph (1). As for the wage to protect workers in question consists of a minimum wage, wages overtime, wages do not work due to absent, wages do not work due to other activities outside of work, wages for exercising the right to take a rest, shape and manner of payment of wages, Fines and deductions from wages, things that can be accounted for by wages, wage structure and scale proportionally, wages for severance payments and wages for income tax calculation.